Concurrent Validity of a Rugby-Specific Yo-Yo Intermittent Recovery Test (Level 1) for Assessing Match-Related Running Performance. Issue 1 (January 2021) - Dobbin, Nick; Highton, Jamie; Moss, Samantha L.; Hunwicks, Richard; Twist, Craig
Abstract : Abstract: Dobbin, N, Highton, J, Moss, SL, Hunwicks, R, and Twist, C. Concurrent validity of a rugby-specific Yo-Yo intermittent recovery test (level 1) for assessing match-related running performance. J Strength Cond Res 35(1): 176–182, 2021—This study investigated the concurrent validity of a rugby-specific high-intensity intermittent running test against the internal, external, and perceptual responses to simulated match play. Thirty-six rugby league players (age 18.5 ± 1.8 years; stature 181.4 ± 7.6 cm; body mass 83.5 ± 9.8 kg) completed the prone Yo-Yo Intermittent Recovery Test (Yo-Yo IR1), of which 16 also completed the Yo-Yo IR1, and 2 × ∼20 minute bouts of a simulated match play (rugby league match simulation protocol for interchange players [RLMSP-i]). Most likely reductions in relative total, low-speed and high-speed distance, mean speed, and time above 20 W·kg −1 (high metabolic power [HMP]) were observed between bouts of the RLMSP-i. Likewise, rating of perceived exertion (RPE) and percentage of peak heart rate (%HRpeak) were very likely and likely higher during the second bout. Pearson's correlations revealed a large relationship for the change in relative distance ( r = 0.57–0.61) between bouts with both Yo-Yo IR1 tests. The prone Yo-Yo IR1 was more strongly related to the RLMSP-i for change in repeated sprint speed ( r = 0.78 cf. 0.56), mean speed ( r = 0.64 cf. 0.36), HMP ( r = 0.48 cf. 0.25), fatigue index ( r = 0.71 cf. 0.63), %HRpeak ( r = −0.56 cf. −0.35), RPEbout1 ( r = −0.44 cf. −0.14), and RPEbout2 ( r = −0.68 cf. −0.41) than the Yo-Yo IR1, but not for blood lactate concentration ( r = −0.20 to −0.28 cf. −0.35 to −0.49). The relationships between prone Yo-Yo IR1 distance and measures of load during the RLMSP-i suggest that it possesses concurrent validity and is more strongly associated with measures of training or match load than the Yo-Yo IR1 using rugby league players.